The development of Irish refugee policy through the prism of the state's foreign policy objectives, 1935 - 1973 - Hegarty, Gianna (Trinity College (Dublin, Ireland). Department of History, 2015)
This dissertation asserts that refugee policy was utilised throughout the mid-twentieth century by the Irish government in order to facilitate the successful pursuit of its foreign policy objectives. The period in question, 1935 to 1973, saw Ireland emerge onto the world stage through an actively pursued policy of international engagement. Irish foreign policy objectives shifted over the decades, yet this study shows that refugee policy was continually, and successfully, used as a political tool by successive Irish governments to influence international perceptions of the country.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin